2011
DOI: 10.5152/tjh.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Influence of detection of pretreatment cytogenetic abnormalities on first complete remission and survival in adult acute lymphoblastic leukemia

Abstract: Objective: Treatment of acute lymphoblastic leukemia (ALL) in adults focuses on the initial assessment of the prognostic relevant cytogenetic features as well as a response-guided therapy based on molecular data. We examined the importance of molecular-cytogenetic abnormalities for complete remission (CR) rates and the overall survival (OS) in adult ALLs. Materials and Methods: Conventional cytogenetics and fluorescence in situ hybridization were performed on bone marrow cells from 33 newly-diagnosed ALL adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…comparatively more than that reported in literature. Our results were similar to the results of another study by Raza et al [18], in which the reported incidence was 85.4%, while our results were in contrast to few other studies conducted in Bangladesh [23], Pakistan [17,19], Turkey [21], Guatemala [22] and India [20] which reported relatively lower incidence.…”
Section: Discussionsupporting
confidence: 90%
“…comparatively more than that reported in literature. Our results were similar to the results of another study by Raza et al [18], in which the reported incidence was 85.4%, while our results were in contrast to few other studies conducted in Bangladesh [23], Pakistan [17,19], Turkey [21], Guatemala [22] and India [20] which reported relatively lower incidence.…”
Section: Discussionsupporting
confidence: 90%
“…The FAB subtype can predict the outcome of patients with AML, with FAB-M2 and FAB-M3 showing relatively better outcomes. The median survival time for the FAB-M3 category was not calculated as less than 50% of events (deaths) occurred by the end of the study period [33,34]. However, this is in contrast to the report by Walter et al, in which the morphological subclassification of AML did not show significant prognostic information for cases of AML [35].…”
Section: Discussionmentioning
confidence: 77%
“…The substantially inferior treatment outcomes in our setup can be primarily attributed to high abandonment, early death (ED), treatment-related mortality rates, and low recovery rates after relapse in the study setting, which commonly result from compromised supportive care and limited capacity, including unavailability of allogeneic stem cell transplantation [26]. In addition, the variation in survival probabilities across the study settings might have resulted from differences in cytogenetic profiles and pathohistological characteristics of the malignancies [32,33,36,37].…”
Section: Discussionmentioning
confidence: 99%